C36. Deep Vein Thrombosis in A Patient with Thrombocytopenia : Case Report. (23rd November 2021) - Mirza, Teuku; Ridwan, Muhammad; Heriansyah, Teuku
Abstract: Background: Deep vein thrombosis (DVT) is a common but elusive illness that can result in suffering and death if not recognized and treated effectively. Overall, 43% of patients with thrombocytopenia were hospitalized, but just 2% of patients had DVT. Case Summary: A 48-year-old male patient presented with a complaint left leg pain accompanied by edema leg 8 days before admission. The patient is a smoker, the patient has a history of diabetes since one year ago, In the laboratory results showed platelet count 23, 000/mm 3, D-dimer above 4000 ng/ml. Anti-dengue IgM and IgG were negative. Doppler examination revealed a thrombus in the common femoral and popliteal veins of the left leg. Patient was treated with low molecular weight heparin (LMWH) Subcutan fondaparinux 5 mg once daily for up to 7 days without bleeding and continued with Rivaroxaban 20 mg once daily, The patient was discharged on day 14. Discussion: Platelet count below 50 x10 9 /L significantly reduces the risk of DVT. Some known risk factors for DVT still appear to apply in patients with thrombocytopenia, and therefore patients with thrombocytopenia would benefit from DVT risk stratification based on platelet count and comorbidity. Patients having thrombocytopenia with DVT were treated safely with anticoagulants without increased occurrence of bleeding. The majority of cases were given therapeutic doses of LMWH.